(3CKQ GdVQjHI GdYGeI Ydi GdeHjYGJ Ydi GdbhI GdGONGQjI aj GdGbJUGO (B/s - (3YHO GdHGSW, YeGQ GdSjOs ((3GdEScfOQjI, eUQ (B:s (3ecJHI GdhaGA GdbGfhfjI,s, 2011)
(3jJfGhd cJGH (B((3CKQ GdVQjHI GdYGeI Ydi GdeHjYGJ Ydi GdbhI GdGONGQjI aj GdGbJUGO(B) (3GdPj bGe HJCdjag YeGQ GdSjO YHO GdHGSW aj MhGdj (B(283) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdVQjHI GdYGeI(B)(3, eJVefG GdehVhYGJ GdJGdjI (B: (3GdJYQja HGdVQjHI GdYGeI Ydi GdeHjYGJ hJWHjbgG aj eUQ, CKQ aQV VQjHI GdeHjYGJ Ydi GdbhI GdGONGQjI aj GdGbJUGO GdeUQj heOi JWhQg, heYOdGJ GdGONGQ GdYGFdj hbWGY GdCYeGd GdNGU hCKQg Ydi JWhQ GdGONGQ Gdbhej(B.s
(3HHdjhLQGajI (B: (3UaMI (B271-279.s
Keywords: (3GdGONGQs -- (3eUQs; (3VQGFH GdeHjYGJs -- (3bhGfjf hJTQjYGJs -- (3eUQs